STRATIFIED WATER-OIL-GAS FLOW THROUGH HORIZONTAL PIPES (Journal of Engineering, 2006)
Stratified three-phase flow through horizontal pipe has been studied experimentally. Thefluids used in the system are water, kerosene, and air. A closed loop flow system, which composedof 0.051 m inside diameter and 4 m length test pipe, is designed with facilities for measuring flowrate, pressure drop and thickness of each phase.The effects of gas, liquid flow rates and water liquid ratio (WLR) have been experimentallyobserved. It was found that liquid (water, and oil) thickness decreased when the gas flow rate isincreased with constant liquid flow rate, and increased when the liquid flow rate is increased atconstant gas flow rate. Pressure drop increased when the gas and/or liquid flow rate is increased.Three equations have been formulated, using the experimental data of the present work, topredict liquid, water thickness and system pressure drop in stratified three-phase flow in horizontalpipe. High correlation coefficients are obtained for these equations.The experimental results are compared with the results obtained from three-phase model ofTaital, Barnea, & Brill (1995). The comparison showed that the predicted data which obtained fromthree-phase flow model Taital et al. (1995) is in good agreement with experimental data.